Advances in small molecule two-photon fluorescent trackers for lipid droplets in live sample imaging - Lee, Dong Joon; Kim, Eun Seo; Lee, Hyo Won; Kim, Hwan Myung (Frontiers in Chemistry, 2022)
Two-photon fluorescent trackers for monitoring of lipid droplets (LDs) would be highly effective for illustrating the critical roles of LDs in live cells or tissues. Although a number of one-photon fluorescent trackers for labeling LDs have been developed, their usability remains constrained in live sample imaging due to photo damage, shallow imaging depth, and auto-fluorescence. Recently, some two-photon fluorescent trackers for LDs have been developed to overcome these limitations. In this mini-review article, the advances in two-photon fluorescent trackers for monitoring of LDs are summarized. We summarize the chemical structures, two-photon properties, live sample imaging, and biomedical applications of the most recent representative two-photon fluorescent trackers for LDs. Additionally, the current challenges and future research trends for the two-photon fluorescent trackers of LDs are discussed.